Management Of Change Communication In Building Positive Perceptions Of The Demographic Bonus - Iswahyu Pranawukir; Agus Hitopa Sukma; Alfan Bachtiar; Misnan Misnan; Hiswanti Hiswanti; Aprih Santoso; Cristino Gusmao (Jurnal Mamangan, 2024)
The demographic bonus is a phenomenon where a country has a population of productive age that is greater than the population of non-productive age. However, to optimize the potential for a demographic bonus, effective management of change communication messages is needed to build positive perceptions among the public. This research aims to analyze and understand how management of change communication messages can play a role in building positive perceptions about the demographic bonus. The research method used is a qualitative approach by collecting data through literature written by communication experts, practitioners and related stakeholders. Apart from that, document analysis and literature studies were also carried out to obtain relevant information. It is hoped that the results of this research will provide better insight and understanding of the importance of managing change communication messages in building positive perceptions about the demographic bonus. Apart from that, it is also hoped that this research can provide practical recommendations in developing effective communication strategies to increase public understanding and participation regarding the demographic bonus. It is hoped that the conclusions of this research can contribute to stakeholders, government and society in optimizing the potential for demographic bonuses effectively and sustainably. With good management of change communication messages, it is hoped that positive perceptions about the demographic bonus can be formed and the public can better understand and support the change efforts needed to make optimal use of the demographic bonus.